Development of a mobile application to improve parents' awareness about unintentional child injuries at home - Neda Sadat Boveir (Archives of Trauma Research, 2025)
Background: Unintentional child injuries commonly occur in or around homes, making parents crucial in preventing, managing, and reducing the adverse consequences of these injuries.Objectives: This study aimed to develop and evaluate a mobile application that supports parents in preventing and caring unintentional child injuries at home.Methods: A literature review was conducted to identify the necessary app requirements. Twelve specialists participated in a survey to determine the app's features. Considering the essential features, an app named Kidoops was designed. A prototype of the app was developed to support parents in the prevention and management of unintentional child home injuries. Finally, satisfaction with Kidoops was assessed among 20 parents with children under 5 years old by a questionnaire for user interaction satisfaction that evaluates the users' subjective satisfaction with the computer interface.Results: The developed app included several approved features aimed at increasing parents' awareness by educating and training them on preventing (checking home safety and prevention tips) and caring (first aid), as well as other useful features such as finding user location and the nearest healthcare centers in case of injuries. The mean score of satisfaction for Kidoops was 7.42 ± 1.08 (out of 9), indicating general satisfaction among parents. The highest score was obtained for system speed, while the lowest score was for the app's flexibility.Conclusion: Kidoops developed based on approved educational and training content, and including useful features can serve as a reliable supplemental tool to empower parents in achieving injury prevention goals at home, in addition to other safety interventions.